Pengembangan Aplikasi Berbasis Android Untuk Monitoring Hasil Belajar Siswa SMK Negeri 3 Malang Oleh Orang Tua - Muhammad Farabi Ismail; Admaja Dwi Herlambang; Satrio Agung Wicaksono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In the process of learning activities in class in general students need an evaluation to measure the extent of academic development. In fact, evaluating learning activities is not only needed by students but also parents. The problem faced by parents is to have their own activities. Parents are not easy to monitor student learning outcomes in real-time and online. The purpose of this study makes it easy for parents to monitor student learning outcomes at school by using Android-based mobile apps. For the development model of the student monitoring application, that is the waterfall. With the requirements specification stage, system design analysis, implementation and testing. The results of developing a student monitoring application have two teacher users and parents. It has an login, reset password, change password, add score, delete score, check comments, check score, leave comments and logout. For testing using 2 methods, black box and user acceptance testing. Black box testing aims at whether all functionalities that have been created when the requirements specification stage is valid or invalid. After testing the black box by running each function, it can be concluded that all functionalities are valid and can be run well. For user acceptance testing, 5 respondents were asked to get direct feedback. This test aims at whether the student monitoring application can be accepted by users to facilitate monitoring student learning outcomes. After testing user acceptance testing, 5 respondents answered 100% YES and the application is acceptable.